From Conventional to Microservices and NVF: A survey of the paradigm shift in IoT Network System Architecture - Subhransu Das, Suman Bhunia, Subhabrata Barman, Santanu Koley, Pinaki Pratim Acharjya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The contents of this paper can be segregated into two major parts. The first part presents a summarized survey of the conventional Wireless Sensor Network (WSN) architectures along with several issues and problems of it. while the second part deals with architectural modifications that is observed modern Internet of Things (IoT) networks. The description of modern IoT network contains the description distributed computing paradigms (such as Edge and Fog computing) along with summarized survey of latest techniques such as Microservices and computational off loadings. The discussion and simulation results led us to enlist some open issues in the concluding section